Role of anisotropic properties on topology optimization of additive manufactured load bearing structures. (1st July 2017) - Zhang, Pu; Liu, Jikai; To, Albert C.
Abstract: Additive manufacturing technology provides a revolutional way of producing engineering structures regardless of their geometric complexity. Hence, topology optimization technique is rapidly becoming a promising tool to design additive manufactured structures to reduce weight and achieve optimal performance simultaneously. However, a common feature of additive manufactured materials is their anisotropy arising from the design and manufacturing process. Therefore, this viewpoint paper aims at presenting an overview of the anisotropy of additive manufactured materials and providing some insights into the role of anisotropy in topology optimization of additive manufactured load-bearing structures.